(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2025)
In this work, we will demonstrate how to design facultative ponds following the method of McGarry & Pescot (1998) to determine their characteristics based on six populations with their respective information. We will also highlight the importance of these ponds as an effective and economical solution for water treatment in various populations. We will describe their features, limitations, application options, and perform calculations and analysis of parameters such as flow rate, BOD (biochemical oxygen demand), the required area for pond design, bacteria purification time, necessary depth, and project efficiency in relation to these parameters, among others. Subsequently, variations will be made in some of these parameters to analyze how they change depending on the population size in each respective population.